PENERAPAN MODEL PEMBELAJARAN PROBING-PROMPTING TERHADAP PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Dodi Rustandi; Ricki Yuliardi; Zuli Nuraeni (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2017)
Improving Student Mathematical Communication Ability.This study used a description test instrument to evaluate students' mathematicalcommunication abilities and used student response questionnaires to find out howstudents respond to the applied learning. To compare the ability of the two classes theresearcher uses one-way t test for two independent samples, Meanwhile, to analyzethe hypothesis of the class gain experiment, researchers used one sample t-test.From the pretest result it was known that the mean score of the experimental class was 4,57 and the control class was 3,79. Through the t-test at that value it is known that thitung = 1,86 while at 5% freedom degree and dk = 86 is known ttabel = 1,99. From both data it was known that -1,99 ? 1,86 ? 1,99 then it meets the acceptance criteria of H0. It means both classes have the initial ability of the same mathematical communication. Meanwhile, from posttest result it was known that the average of experiment class score was 11,53 and control class was 7,57. Because the posttest scores of the experimental class and homogeneous controls, then the comparative test was performed by the t-test. From the t-test it was known that thitung = 3,81 and ttabel = 1,67. From both data it was known that thitung ? ttable then thitung was not available in the reception area H0. This means that after the treatment of students' mathematical communication abilities, the experimental class was better than the control class. The improvement of mathematical communication ability of experimental class students were in the medium category. In addition, from the results of questionnaire responses of students, it was known that students showed a positive response to the probing-prompting learning model.